Analysis of Work Posture and Manual Handling on the Material Transport Activities of Indonesian Traditional Market Worker - Kurnianingtyas, Chandra Dewi; Sukma, Heydar Pradika (Universitas Atma Jaya Yogyakarta, 2022)
This research is about the observation of workers transporting sacks in a traditional market. The worker complained about pain in many body parts like the shoulders, waist, and arms, which are presented in the results of the Nordic Body Map questionnaire. This problem can be solved by massaging the body section to reduce musculoskeletal disorders. Because it is often get massaged, it makes the completion time of sack transport become longer. Work posture must be improved because too much pain piles up over long periods and can impact condition health and decrease productivity. The purpose of this research is to evaluate the working posture while doing manual handling. Evaluate work posture using Rapid Entire Body Assessment (REBA) and Manual Handling Assessment Chart (MAC Tool). As a result, work posture and manual handling have a higher level of risk of injury, so we need to investigate and implement change. The level of risk must be reduced to at least medium risk. Using auxiliaries can improve work posture, reduce health risks, reduce load sacks, and increase work productivity. The recommended outcome is adding a skid box to improve the value of REBA and manual material handling by providing a hand trolley cart.